Personnel Triangulation Using Adaptive Machine Learning - HAIRUZAMAN, MOHAMMAD HAFI (IRC, 2019)
Adaptive Machine Learning is a branch of neural network which develop a system to mimic the human neural system into the machines or can be called as Artificial Intelligence. Currently, AML is vastly developing and implemented into the machines such as mobile phones, computers, games and so on. As for the personnel triangulation, it is a system used to detect human movements either inside or outside a building. Personnel triangulation consists of two classes which is OPS and IPS. OPS stand for Outdoor Positioning System while IPS is Indoor Positioning System. OPS use GPS or GNSS, from multiple satellites to track down the devices that have the GPS capability, but it is mostly unusable inside a building because of a few causes. But for IPS, there is yet a system used to accurately track the exact tracking device positions. So, by applying AML into the personnel triangulation system, an accurate system might be created to track personnel inside a building and improving the tracking system especially for IPS tracking classes.